A kind of silicon-free release PET film and preparation method thereof

By adding modified alumina and chloroether rubber derivatives to silicon-free release PET films, the problems of degraded mechanical properties and insufficient flame retardancy of the film are solved, and higher mechanical properties and flame retardant properties are achieved, and the use is extended. life.

CN118810182BActive Publication Date: 2025-02-21GUANGDONG BAOJIALI COLOR PRINTING IND CO LTD

Patent Information

Application Number
CN202410807610.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-21
Publication Date
2025-02-21
Estimated Expiration
2044-06-21

AI Technical Summary

Technical Problem

After the silicon-free release PET film has a reduced mechanical properties and poor flame retardancy after bearing various external forces.

Method used

By adding inorganic modified filler and composite additives to the PET film, alumina and chloroether rubber are respectively modified to form a film with improved interface performance and flame retardant properties.

Benefits of technology

It improves the mechanical properties and flame retardant properties of the film, extends the service life, and maintains stability and reliability in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118810182B_ABST
    Figure CN118810182B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of release films, and discloses a silicon-free release PET film and a preparation method thereof. The silicon-free release PET film comprises a polymer wax layer, an intermediate layer and a polymer wax layer in order from top to bottom; the intermediate layer is made of the following raw materials: PET, an inorganic modified filler, a composite additive and an antioxidant 1010; wherein the inorganic modified filler is prepared by grafting polyamide-amine onto the surface of aluminum oxide, thereby improving the mechanical properties and high temperature resistance of the film, and avoiding the film from cracking or breaking when subjected to external force; the composite additive is prepared by preparing a chloroether rubber derivative containing nitrogen and phosphorus flame retardants in the structure, thereby improving the toughness and flame retardant properties of the film, and the comprehensive play of these effects enables the silicon-free release PET film to maintain excellent performance and stability and have a long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of release films, and in particular to a silicon-free release PET film and a preparation method thereof. Background Art

[0002] Release film, also known as peeling film or isolation film, is a functional film with a plastic film as the substrate, and a release agent and glue are coated on one or both sides of the film to make it non-sticky or slightly sticky to specific materials under limited conditions. The substrates of general plastic films include PET, PE, PP, PTFE and BOPP. Among them, polyethylene terephthalate (PET) has become a commonly used material for preparing high-performance release films due to its excellent thermal stability, small thickness tolerance and high transparency. Traditional release films are usually made of silicone resin and are coated on the surface of the mold to form an isolation layer so that the molded part and the mold surface are not in direct contact. The silicone-free release PET film does not contain silicone. PET is used as the raw material, and polymer wax materials are added to the surface during the film making process. Compared with traditional release films, this silicone-free release film has the advantages of good release effect, environmental protection and no residue, strong temperature resistance and high production efficiency. It is widely used in printed circuit boards, FPC flexible circuit boards, electronics and electrical, printing and packaging, pharmaceuticals, tape bonding and other fields.

[0003] With the rapid development of the industrial field, the use scope of release films is becoming wider and wider, and there are certain requirements for their other properties. During long-term use, the silicone-free release PET film needs to withstand various external forces, and its mechanical properties such as strength and toughness may decrease. Therefore, it is necessary to improve the mechanical properties of the silicone-free release PET film to avoid cracks or breakage to ensure that it can meet the needs of various industrial applications. In addition, silicone-free release PET film is often used in circuit boards, electronic and electrical fields. Therefore, the silicone-free release PET film needs to have certain flame retardant properties to slow down the burning speed when a fire occurs, thereby reducing the destructiveness of the fire and the risk of casualties.

[0004] The publication number is CN117024806B, a method for preparing a high temperature resistant enhanced PET release film, which adds cerium-barium co-modified ZrO 2 The synergistic effect of particles, cerium and barium can promote the 2 The particles form stable clusters or particles, preventing ZrO 2 The growth of grains and the diffusion of grain boundaries can improve the thermal stability and antioxidant properties of the material, effectively increase the tensile strength and hardness of the material, thereby improving durability and mechanical properties. Therefore, a high-performance silicone-free release PET film can be prepared by adding other functional additives to the matrix. Summary of the invention

[0005] The purpose of the present invention is to provide a silicon-free release PET film and a preparation method thereof, which solves the following technical problems:

[0006] (1) Solved the problem that the mechanical properties of the silicone-free release PET film deteriorated due to various external forces;

[0007] (2) The problem of poor flame retardancy of silicone-free release PET film has been solved.

[0008] The purpose of the present invention can be achieved through the following technical solutions:

[0009] A silicon-free release PET film, which comprises a polymer wax layer, an intermediate layer, and a polymer wax layer in order from top to bottom; the intermediate layer is made of the following raw materials in parts by weight: 40 to 60 parts of PET, 7 to 9 parts of inorganic modified filler, 4 to 6 parts of composite additives, and 1 to 2 parts of antioxidant 1010;

[0010] The polymer wax layer is formed by mixing polyethylene wax and PET as raw materials and then melt extruding; the weight of the polyethylene wax is 60 parts and the weight of the PET is 30 parts, or the weight of the polyethylene wax is 70 parts and the weight of the PET is 35 parts, or the weight of the polyethylene wax is 80 parts and the weight of the PET is 40 parts;

[0011] Furthermore, the preparation method of the inorganic modified filler comprises the following steps:

[0012] A1: Add alumina to xylene solution, ultrasonically disperse for 15-35 minutes, pass nitrogen protection, add 4-bromobutyric acid and esterification catalyst, after addition, raise the system temperature to 105-115°C, stir for 5-7 hours, wait for the material to cool naturally, centrifuge to separate the solid material, wash the solid material, and vacuum dry to obtain modified alumina;

[0013] A2: Add modified alumina and dimethyl sulfoxide solution into a reactor, perform ultrasound to form a uniform mixed solution, then add polyamide-amine and alkaline catalyst into the mixed solution, pass nitrogen, exhaust the air, raise the temperature to 60-70°C, keep stirring at this temperature for 4-6 hours, filter, collect the product, and dry to obtain an inorganic modified filler.

[0014] Furthermore, in step A1, the particle size of the aluminum oxide is 1 to 10 μm.

[0015] Furthermore, in step A1, the esterification catalyst is any one of calcium methanesulfonate, p-toluenesulfonic acid, aminosulfonic acid or tetrabutyl titanate.

[0016] Furthermore, in step A1, the mass ratio of the aluminum oxide to 4-bromobutyric acid is 1:0.2-0.7.

[0017] Furthermore, in step A2, the alkaline catalyst is any one of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate.

[0018] Through the above technical scheme, the hydroxyl groups on the surface of alumina can react with the carboxyl groups in the 4-bromobutyric acid structure under the action of an esterification catalyst, thereby introducing halogen groups on the surface of alumina to obtain modified alumina. Under the action of an alkaline catalyst, the halogen groups on the surface of the modified alumina react with the amino groups in the polyamide-amine structure to obtain an inorganic modified filler.

[0019] Furthermore, the preparation method of the composite additive comprises the following steps:

[0020] AA1: Place chloroether rubber in toluene, stir evenly, raise the temperature to 60-70°C, add dimethylaminoethyl acrylate, keep stirring for 6-8 hours, and remove the solvent by reduced pressure distillation to obtain modified chloroether rubber;

[0021] AA2: Place modified chloroether rubber and ammonium hexafluorophosphate in a reaction kettle, add an organic solvent, stir evenly with a magnetic stirrer, react at room temperature for 10 to 12 hours, and discharge the material to obtain a composite additive.

[0022] Furthermore, in step AA1, the number average molecular weight of the chloroether rubber is 8000 to 12000.

[0023] Furthermore, in step AA2, the organic solvent is any one of acetonitrile or methanol.

[0024] Through the above technical scheme, the active chlorine in the epichlorohydrin rubber structure can undergo a quaternization reaction with the tertiary amine in the dimethylaminoethyl acrylate structure to obtain a modified epichlorohydrin rubber with a quaternary ammonium group. In an organic solvent, the modified epichlorohydrin rubber undergoes an ion exchange reaction with ammonium hexafluorophosphate to obtain a composite additive.

[0025] A method for preparing a silicon-free release PET film comprises the following steps:

[0026] (1) PET, inorganic modified filler, composite additive, and antioxidant 1010 are added to a mixer and mixed to form a mixture A, and the mixture A is transferred to an extruder and melted at a melting temperature of 260 to 270° C. to obtain an intermediate layer, and polyethylene wax and PET are placed in a mixer and stirred to obtain a mixture B, and the mixture B is then placed in an extruder and melted at a melting temperature of 255 to 265° C. to obtain a polymer wax layer;

[0027] (2) using a three-layer co-extrusion technology, the obtained intermediate layer and polymer wax layer flow out through a T-shaped die and are quickly attached to the surface of a chilled roller to form a solid sheet to obtain a base film;

[0028] (3) placing the base film obtained in step (2) in a stretching machine, first stretching it longitudinally, and then stretching it transversely to form a biaxially stretched PET film;

[0029] (4) measuring the thickness of the biaxially stretched PET film, performing a traction process, and then rolling it into a semi-finished product;

[0030] (5) The rolled semi-finished product is placed in an environment with a temperature of 25 to 35° C. and a relative humidity of 65% to 75% RH for aging treatment for 36 to 60 hours, and then cut into small rolls according to the required width, which is the silicon-free release PET film.

[0031] Beneficial effects of the present invention:

[0032] (1) The present invention obtains an inorganic modified filler by grafting polyamide-amine on the surface of aluminum oxide, and adds the inorganic modified filler to the preparation process of the silicon-free release PET film. After the aluminum oxide surface is organically modified, the interface performance between it and the PET matrix is ​​enhanced, which helps the inorganic modified filler to be evenly dispersed in the PET matrix, avoiding the phase separation phenomenon between the two phases due to interface problems. The aluminum oxide in the inorganic modified filler can not only improve the strength of the film, avoiding the phenomenon of cracks or damage to the silicon-free release PET film when subjected to external forces, but also improve the hardness of the film, avoiding the phenomenon of serious scratches caused by slight scratches. The polyamide-amine in the inorganic modified filler has a dendritic structure, which further improves the mechanical properties of the film. At the same time, the silicon-free release PET film has good high temperature resistance, so as to ensure that it can still maintain stability and reliability in a high temperature environment, thereby extending its service life.

[0033] (2) The present invention prepares a chloroether rubber derivative containing nitrogen and phosphorus flame retardants as a composite additive. The rubber segment in the composite additive can absorb stress, thereby improving the toughness of the silicone-free release PET film, preventing the silicone-free release PET film from deformation or breakage, and further enhancing the mechanical strength of the silicone-free release PET film. In addition, the composite additive structure contains nitrogen and phosphorus flame retardant elements, which give the silicone-free release PET film additional flame retardant properties. According to tests, the silicone-free release PET film has a limiting oxygen index of up to 33.4%, which can slow down the combustion speed when a fire occurs, thereby reducing the destructiveness of the fire and the risk of casualties.

[0034] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0036] Figure 1 This is a scanning electron microscope image of the alumina and inorganic modified filler prepared in Example 1 of the present invention.

[0037] Figure 2 This is an infrared spectrum test chart of the composite additive prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] 1. Preparation of inorganic modified fillers

[0041] A1: 3 g of alumina with a particle size of 5 μm was added to a xylene solution, and ultrasonically dispersed for 25 min. Under nitrogen protection, 1.1 g of 4-bromobutyric acid and 0.08 g of tetrabutyl titanate were added. After the addition, the system temperature was raised to 110°C and stirred for 6 h. After the material was cooled naturally, the solid material was separated by centrifugation, washed, and vacuum dried to obtain modified alumina;

[0042] A2: Add 5 g of modified alumina and dimethyl sulfoxide solution into the reactor, perform ultrasound to form a uniform mixed solution, then add 3.2 g of polyamide-amine and 0.1 g of sodium carbonate into the mixed solution, pass nitrogen, expel the air, raise the temperature to 65°C, keep stirring at this temperature for 5 h, filter, collect the product, and dry to obtain an inorganic modified filler.

[0043] A Japanese HITACHIS4700 scanning electron microscope was used to analyze the morphology of alumina and inorganic modified fillers. The test results are shown in Figure 1 As can be seen from the figure, the surface of alumina is smooth, while the surface of inorganic modified filler is rough. This is because polyamide-amine is grafted onto the surface of alumina.

[0044] 2. Preparation of composite additives

[0045] AA1: 10 g of chloroether rubber with a number average molecular weight of 8000 was placed in toluene, stirred evenly, and the temperature was raised to 65°C. Then 0.6 g of dimethylaminoethyl acrylate was added, and the mixture was stirred at the temperature for 7 hours. The solvent was removed by distillation under reduced pressure to obtain a modified chloroether rubber;

[0046] AA2: Weigh 5 g of modified chloroether rubber and 2.6 g of ammonium hexafluorophosphate into a reaction kettle, add methanol solution, stir evenly with magnetic force, react at room temperature for 11 h, and discharge to obtain a composite additive.

[0047] The composite additives were tested using a Nicolet 510P infrared spectrometer. The test results are shown in Figure 2 ,Depend on Figure 2 It can be seen that in the infrared spectrum of the composite additive, 3020cm -1 The characteristic absorption peak of the carbon-hydrogen bond in the carbon-carbon double bond appears at 1741 cm -1 The characteristic absorption peak of the ester group C=O appears at 1060cm -1 The characteristic absorption peak of ether bond COC appears at 1405 cm -1 The characteristic absorption peak of CN in quaternary ammonium salt appears at 839cm -1 PF 6 - absorption peak.

[0048] 3. Preparation of Silicone-free Release PET Film

[0049] (1) 40 g of PET, 7 g of inorganic modified filler, 4 g of composite additive, and 1 g of antioxidant 1010 were added to a mixer and mixed to form a mixture, and the mixture was transferred to an extruder for melting at a melting temperature of 260° C. to obtain an intermediate layer, 60 g of polyethylene wax and 30 g of PET were placed in a mixer and stirred evenly to obtain a mixture B, and the mixture B was placed in an extruder for melting at a melting temperature of 255° C. to obtain a polymer wax layer;

[0050] (2) Using three-layer co-extrusion technology, the middle layer and the polymer wax layer flow out through a T-shaped die and are quickly attached to the surface of a chilled roller to form a solid sheet to obtain a base film;

[0051] (3) placing the base film obtained in step (2) in a stretching machine, first stretching it longitudinally, and then stretching it transversely to form a biaxially stretched PET film;

[0052] (4) measuring the thickness of the biaxially stretched PET film, performing a traction process, and then rolling it into a semi-finished product;

[0053] (5) The rolled semi-finished product is placed in an environment with a temperature of 25° C. and a relative humidity of 65% RH for aging treatment for 36 hours, and then cut into small rolls according to the required width, which is the silicon-free release PET film.

[0054] Example 2

[0055] Preparation of Silicone-free Release PET Film

[0056] (1) 50 g of PET, 8 g of inorganic modified filler, 5 g of composite additive, and 1.5 g of antioxidant 1010 were added to a mixer and mixed to form a mixture, and the mixture was transferred to an extruder for melting at a melting temperature of 265° C. to obtain an intermediate layer, 70 g of polyethylene wax and 35 g of PET were placed in a mixer and stirred evenly to obtain a mixture B, and the mixture B was placed in an extruder for melting at a melting temperature of 260° C. to obtain a polymer wax layer;

[0057] (2) Using three-layer co-extrusion technology, the middle layer and the polymer wax layer flow out through a T-shaped die and are quickly attached to the surface of a chilled roller to form a solid sheet to obtain a base film;

[0058] (3) placing the base film obtained in step (2) in a stretching machine, first stretching it longitudinally, and then stretching it transversely to form a biaxially stretched PET film;

[0059] (4) measuring the thickness of the biaxially stretched PET film, performing a traction process, and then rolling it into a semi-finished product;

[0060] (5) The rolled semi-finished product is placed in an environment with a temperature of 30° C. and a relative humidity of 70% RH for aging treatment for 48 hours, and then cut into small rolls according to the required width, which is the silicon-free release PET film.

[0061] The preparation method of the inorganic modified filler and the composite additive is the same as that in Example 1.

[0062] Example 3

[0063] Preparation of Silicone-free Release PET Film

[0064] (1) 60 g of PET, 9 g of inorganic modified filler, 6 g of composite additive, and 2 g of antioxidant 1010 were added to a mixer and mixed to form a mixture, and the mixture was transferred to an extruder for melting at a melting temperature of 270° C. to obtain an intermediate layer, 80 g of polyethylene wax and 40 g of PET were placed in a mixer and stirred evenly to obtain a mixture B, and the mixture B was placed in an extruder for melting at a melting temperature of 265° C. to obtain a polymer wax layer;

[0065] (2) Using three-layer co-extrusion technology, the middle layer and the polymer wax layer flow out through a T-shaped die and are quickly attached to the surface of a chilled roller to form a solid sheet to obtain a base film;

[0066] (3) placing the base film obtained in step (2) in a stretching machine, first stretching it longitudinally, and then stretching it transversely to form a biaxially stretched PET film;

[0067] (4) measuring the thickness of the biaxially stretched PET film, performing a traction process, and then rolling it into a semi-finished product;

[0068] (5) The rolled semi-finished product is placed in an environment with a temperature of 35° C. and a relative humidity of 75% RH for aging treatment for 60 hours, and then cut into small rolls according to the required width, which is the silicon-free release PET film.

[0069] The preparation method of the inorganic modified filler and the composite additive is the same as that in Example 1.

[0070] Comparative Example 1

[0071] Preparation of Silicone-free Release PET Film

[0072] (1) 50 g of PET, 8 g of inorganic modified filler, and 1.5 g of antioxidant 1010 were added to a mixer and mixed to form a mixture, and the mixture was transferred to an extruder for melting at a melting temperature of 265° C. to obtain an intermediate layer, 70 g of polyethylene wax and 35 g of PET were placed in a mixer and stirred evenly to obtain a mixture B, and the mixture B was placed in an extruder for melting at a melting temperature of 260° C. to obtain a polymer wax layer;

[0073] (2) Using three-layer co-extrusion technology, the middle layer and the polymer wax layer flow out through a T-shaped die and are quickly attached to the surface of a chilled roller to form a solid sheet to obtain a base film;

[0074] (3) placing the base film obtained in step (2) in a stretching machine, first stretching it longitudinally, and then stretching it transversely to form a biaxially stretched PET film;

[0075] (4) measuring the thickness of the biaxially stretched PET film, performing a traction process, and then rolling it into a semi-finished product;

[0076] (5) The rolled semi-finished product is placed in an environment with a temperature of 30° C. and a relative humidity of 70% RH for aging treatment for 48 hours, and then cut into small rolls according to the required width, which is the silicon-free release PET film.

[0077] The preparation method of the inorganic modified filler is the same as that in Example 1.

[0078] Comparative Example 2

[0079] Preparation of Silicone-free Release PET Film

[0080] (1) 50 g of PET, 5 g of composite additive, and 1.5 g of antioxidant 1010 were added to a mixer and mixed to form a mixture, and the mixture was transferred to an extruder and melted at a melting temperature of 265° C. to obtain an intermediate layer, 70 g of polyethylene wax and 35 g of PET were placed in a mixer and stirred evenly to obtain a mixture B, and the mixture B was placed in an extruder and melted at a melting temperature of 260° C. to obtain a polymer wax layer;

[0081] (2) Using three-layer co-extrusion technology, the middle layer and the polymer wax layer flow out through a T-shaped die and are quickly attached to the surface of a chilled roller to form a solid sheet to obtain a base film;

[0082] (3) placing the base film obtained in step (2) in a stretching machine, first stretching it longitudinally, and then stretching it transversely to form a biaxially stretched PET film;

[0083] (4) measuring the thickness of the biaxially stretched PET film, performing a traction process, and then rolling it into a semi-finished product;

[0084] (5) The rolled semi-finished product is placed in an environment with a temperature of 30° C. and a relative humidity of 70% RH for aging treatment for 48 hours, and then cut into small rolls according to the required width, which is the silicon-free release PET film.

[0085] The preparation method of the composite additive is the same as that in Example 1.

[0086] Comparative Example 3

[0087] Preparation of Silicone-free Release PET Film

[0088] (1) 50 g of PET, 5 g of aluminum oxide, 5 g of composite additive, and 1.5 g of antioxidant 1010 were added to a mixer and mixed to form a mixture, and the mixture was transferred to an extruder and melted at a melting temperature of 265° C. to obtain an intermediate layer, 70 g of polyethylene wax and 35 g of PET were placed in a mixer and stirred to obtain a mixture B, and the mixture B was placed in an extruder and melted at a melting temperature of 260° C. to obtain a polymer wax layer;

[0089] (2) Using three-layer co-extrusion technology, the middle layer and the polymer wax layer flow out through a T-shaped die and quickly adhere to the surface of a chilled roller to form a solid sheet to obtain a base film;

[0090] (3) placing the base film obtained in step (2) in a stretching machine, first stretching it longitudinally, and then stretching it transversely to form a biaxially stretched PET film;

[0091] (4) measuring the thickness of the biaxially stretched PET film, performing a traction process, and then rolling it into a semi-finished product;

[0092] (5) The rolled semi-finished product is placed in an environment with a temperature of 30° C. and a relative humidity of 70% RH for aging treatment for 48 hours, and then cut into small rolls according to the required width, which is the silicon-free release PET film.

[0093] The preparation method of the composite additive is the same as that in Example 1.

[0094] Comparative Example 4

[0095] Preparation of Silicone-free Release PET Film

[0096] (1) 50 g of PET and 1.5 g of antioxidant 1010 were added to a mixer and mixed to form a mixture, and the mixture was transferred to an extruder for melting at a melting temperature of 265° C. to obtain an intermediate layer, and 35 g of PET was placed in an extruder for melting at a melting temperature of 260° C. to obtain a polymer wax layer;

[0097] (2) Using three-layer co-extrusion technology, the middle layer and the polymer wax layer flow out through a T-shaped die and quickly adhere to the surface of a chilled roller to form a solid sheet to obtain a base film;

[0098] (3) placing the base film obtained in step (2) in a stretching machine, first stretching it longitudinally, and then stretching it transversely to form a biaxially stretched PET film;

[0099] (4) measuring the thickness of the biaxially stretched PET film, performing a traction process, and then rolling it into a semi-finished product;

[0100] (5) The rolled semi-finished product is placed in an environment with a temperature of 30° C. and a relative humidity of 70% RH for aging treatment for 48 hours, and then cut into small rolls according to the required width, which is the silicon-free release PET film.

[0101] Performance Testing

[0102] The silicon-free release PET films prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 4 were subjected to the following performance tests:

[0103] ① The impact strength is tested according to GB / T 1043.1-2008 "Determination of impact properties of simply supported beams of plastics Part 1: Non-instrumented impact test"; the hardness is tested according to GB / T2411-2008 "Plastics and hard rubber - Determination of indentation hardness (Shore hardness) using a durometer"; the tensile properties are tested according to GB / T 1040.1-2018 "Determination of tensile properties of plastics Part 1: General principles". The specific test results are shown in the table below:

[0104]

[0105] From the test data in the analysis table, it can be seen that the silicon-free release PET films prepared in Examples 1 to 3 have good mechanical properties and toughness; since Comparative Example 1 does not use a composite additive as a modifier, the toughness of the film is poor compared with the example, but an inorganic modified filler is added thereto, so the film has good mechanical properties; Comparative Example 2 does not use an inorganic modified filler as a modifier, and the mechanical properties of the film are poor compared with the example, but a composite additive is added thereto, so the film has good toughness; Comparative Example 3 uses a composite additive and alumina for filling, which may have compatibility problems, so the mechanical properties of the film are reduced; Comparative Example 4 prepares a silicon-free release PET film, neither an inorganic modified filler nor a composite additive is added, so the mechanical properties and toughness of the film are poor.

[0106] ② The flame retardant performance is tested according to GB / T2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test"; the high temperature resistance is tested according to GB / T1633-2000 "Determination of Vicat softening temperature (VST) of thermoplastics"; the surface wetting tension is tested according to GB / T14216-2008 "Determination of wetting tension of plastic films and sheets". The specific test results are shown in the table below:

[0107] Limiting oxygen index (%) Vicat softening temperature(℃) Wetting tension (mN / m) Example 1 33.2 218 29 Example 2 33.4 220 27 Example 3 32.8 216 26 Comparative Example 1 25.7 214 27 Comparative Example 2 31.3 182 28 Comparative Example 3 30.9 195 27 Comparative Example 4 20.6 170 36

[0108] From the test data in the analysis table, it can be seen that the limiting oxygen index value of the silicon-free release PET film prepared in Examples 1 to 3 is above 32%, and the Vicat softening temperature value is above 215°C. Among them, the higher the wax content, the lower the surface wetting tension of the film, so the film has good high temperature resistance, flame retardancy and surface wetting tension; the silicon-free release PET film prepared in Comparative Example 1 does not add composite additives, and the flame retardancy of the film is poor compared with the embodiment, but inorganic modified fillers are added therein, so the film has good high temperature resistance and good surface wetting tension performance; the silicon-free release PET film prepared in Comparative Example 2 does not add composite additives, and the flame retardancy of the film is poor compared with the embodiment, but inorganic modified fillers are added therein, so the film has good high temperature resistance and good surface wetting tension performance. Inorganic modified fillers are added, and the high temperature resistance of the film is poor compared with that in the embodiment, but composite additives are added therein, so the film has good flame retardancy and good surface wetting tension performance; in Comparative Example 3, composite additives and alumina are used for filling, and compared with the embodiment, the flame retardancy and surface wetting tension of the film are good, but the high temperature resistance is poor; the silicone-free release PET film prepared in Comparative Example 4 does not contain inorganic modified fillers and composite additives, and no polyethylene wax is added during the preparation of the polymer wax layer, so the flame retardancy, high temperature resistance and surface wetting tension of the film are all poor.

[0109] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A silicon-free release PET film, characterized in that: The silicon-free release PET film includes a polymer wax layer, an intermediate layer, and a polymer wax layer from top to bottom; the intermediate layer is made of the following raw materials in parts by weight: 40 to 60 parts of PET, 7 to 9 parts of inorganic modified fillers, 4 to 6 parts of composite additives, and 1 to 2 parts of antioxidant 1010; The polymer wax layer is formed by mixing polyethylene wax and PET as raw materials and then melt extruding; the weight of the polyethylene wax is 60 parts and the weight of the PET is 30 parts, or the weight of the polyethylene wax is 70 parts and the weight of the PET is 35 parts, or the weight of the polyethylene wax is 80 parts and the weight of the PET is 40 parts; The preparation method of the inorganic modified filler comprises the following steps: A1: Add alumina to xylene solution, ultrasonically disperse for 15-35 minutes, pass nitrogen protection, add 4-bromobutyric acid and esterification catalyst, after addition, raise the system temperature to 105-115°C, stir for 5-7 hours, wait for the material to cool naturally, centrifuge to separate the solid material, wash the solid material, and vacuum dry to obtain modified alumina; A2: Add modified alumina and dimethyl sulfoxide solution into a reactor, perform ultrasound to form a uniform mixed solution, then add polyamide-amine and alkaline catalyst into the mixed solution, pass nitrogen, exhaust air, raise the temperature to 60-70°C, keep stirring at this temperature for 4-6 hours, filter, collect the product, and dry to obtain an inorganic modified filler; The esterification catalyst is any one of calcium methanesulfonate, p-toluenesulfonic acid, aminosulfonic acid or tetrabutyl titanate; The mass ratio of the aluminum oxide to 4-bromobutyric acid is 1:0.2-0.7; The alkaline catalyst is any one of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate; The preparation method of the composite additive comprises the following steps: AA1: Place chloroether rubber in toluene, stir evenly, raise the temperature to 60-70°C, add dimethylaminoethyl acrylate, keep stirring for 6-8 hours, and remove the solvent by reduced pressure distillation to obtain modified chloroether rubber; AA2: Place modified chloroether rubber and ammonium hexafluorophosphate in a reaction kettle, add an organic solvent, stir evenly with a magnetic force, react at room temperature for 10 to 12 hours, and discharge to obtain a composite additive; The number average molecular weight of the chloroether rubber is 8000-12000.

2. A silicon-free release PET film according to claim 1, characterized in that: In step A1, the particle size of the aluminum oxide is 1 to 10 μm.

3. The silicon-free release PET film according to claim 1, characterized in that: In step AA2, the organic solvent is any one of acetonitrile or methanol.

4. A method for preparing a silicon-free release PET film as claimed in claim 1, characterized in that: The following steps are involved: (1) PET, inorganic modified filler, composite additive, and antioxidant 1010 are added to a mixer and mixed to form a mixture A, and the mixture A is transferred to an extruder and melted at a melting temperature of 260 to 270° C. to obtain an intermediate layer, and polyethylene wax and PET are placed in a mixer and stirred to obtain a mixture B, and the mixture B is then placed in an extruder and melted at a melting temperature of 255 to 265° C. to obtain a polymer wax layer; (2) using a three-layer co-extrusion technology, the obtained intermediate layer and polymer wax layer flow out through a T-shaped die and are quickly attached to the surface of a chilled roller to form a solid sheet to obtain a base film; (3) placing the base film obtained in step (2) in a stretching machine, first stretching it longitudinally, and then stretching it transversely to form a biaxially stretched PET film; (4) measuring the thickness of the biaxially stretched PET film, performing a traction process, and then rolling it into a semi-finished product; (5) The rolled semi-finished product is placed in an environment with a temperature of 25 to 35° C. and a relative humidity of 65% to 75% RH for aging treatment for 36 to 60 hours, and then cut into small rolls according to the required width, which is the silicon-free release PET film.

Citation Information

Patent Citations

  • A method for preparing high temperature resistant enhanced PET release film

    CN117024806B

  • Completely biodegradable high-barrier polyamide-based composite film material and preparation method thereof

    CN110982259A

  • Method to enable nanoparticles stored with a specific type of assembly to maintain this type of assembly upon reconstitution

    US20240165234A1

Cited By

  • Release master batch internally added with non-silicon, preparation method of release master batch and release film with nanoscale roughness

    CN121975279A

  • Non-silicon release masterbatch, method of making, and nano-roughness release film

    CN121975279B